The Contributions of Feminist Theory in Advancing the Field of International Relations - fikram rettob (Jurnal Ilmu Politik dan Studi Sosial Terapan, 2025)
Feminist theory introduces a critical and transformative perspective to the international sphere, offering a nuanced understanding of global politics. Recognising its contributions is essential for comprehensively analysing contemporary global challenges. This study aims to highlight the significance of feminist ideas. Despite often being marginalised in dominant political discourses of masculinity, feminist ideas provide some of the most equitable and effective solutions for addressing global issues. Feminist perspectives challenge traditional power structures, advocate for gender justice, and promote inclusivity in political decision-making. By examining these contributions, this research seeks to emphasise the importance of integrating feminist approaches into global political frameworks. Utilising a qualitative methodology, the study is grounded in original content analysis and deductive way, drawing upon credible sources, including books, peer-reviewed journals, scholarly articles, and official written statements. Through this approach, the study underscores the necessity of feminist theory in constructing a more just and balanced global political landscape.